DIGITAL QUEUE SYSTEM DESIGN BASED MIKROKONTROLER AT89S51 - Sapto Mujoko; Fivtatianti Hendajani. SKom., MM (Jurnal Sistem Informasi, 2009)
Series of "Design of Microcontroller Based Digital Queue System AT89S51 "function to help create an atmosphere that is safe, comfortable and compliant at the time of the queue for a particular transaction. This tool is designed with the input of a switch, data processing using AT89S51 Microcontroller IC, and output display  and buzzer as an indicator seven-segment detecting the number of queues. This tool works by detecting a pressure switch input, then the microcontroller will process input into the input data which would then be used to perform the counting process and the results will be displayed on the seven-segment indicator with buzzer that sounds. Views on the seven segments of this function is to provide information to visitors (queue) that the numbers that appear in the seven-segment display shows the queue number that will make transactions.